2020
DOI: 10.15416/pcpr.v5i1.25624
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Docking Study of 1-(3-Chloropropyl)-3,5-Bis((E)-4-Methoxybenzylidene)Piperidin-4-One as Dengue Virus Type 2 (DEN2) NS2B/NS3 Protease Inhibitor Candidate

Abstract: Curcumin is a secondary metabolite compound that has diverse biological activities. However, it is easily hydrolyzed at physiological pH due to the presence of the β-diketone group. Therefore, the replacement of the β-diketone group with mono ketone is expected to overcome this issue. We hereby report the synthesis of mono ketone curcumin derivatives from piperidone by two-steps reactions. The synthesis of curcumin derivate 3 was carried out by Claisen-Schmidt condensation between 4-piperidone and 4-methoxyben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…With an unidentified mechanism that may entail interactions with NS4A and NS4B, NS1 protein seems to be crucial for viral replication (Chen et al, 2018). Most of the in silico and in vitro studies demonstrated that NS2B/NS3 as well as NS5 and NS1 proteins are targeted by curcumin (Ariza et al, 2014; Habibi et al, 2020; Lim et al, 2020; Lima et al, 2017). Other studies suggest that the cytoskeleton arrangement, the ubiquitin‐proteasome system, and the apoptotic process are altered by curcumin in DENV‐infected cells (Chen et al, 2013; Halim et al, 2021; Padilla‐S et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With an unidentified mechanism that may entail interactions with NS4A and NS4B, NS1 protein seems to be crucial for viral replication (Chen et al, 2018). Most of the in silico and in vitro studies demonstrated that NS2B/NS3 as well as NS5 and NS1 proteins are targeted by curcumin (Ariza et al, 2014; Habibi et al, 2020; Lim et al, 2020; Lima et al, 2017). Other studies suggest that the cytoskeleton arrangement, the ubiquitin‐proteasome system, and the apoptotic process are altered by curcumin in DENV‐infected cells (Chen et al, 2013; Halim et al, 2021; Padilla‐S et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the in silico and in vitro studies demonstrated that NS2B/ NS3 as well as NS5 and NS1 proteins are targeted by curcumin (Ariza et al, 2014;Habibi et al, 2020;Lim et al, 2020;Lima et al, 2017).…”
Section: Dengue Virusmentioning
confidence: 99%
“…In search of potential drug candidates against protein than the positive control panduratin A (−5.18 kcal/mol). [171] This diarylpentanoid derivative also forms hydrophobic and hydrophilic interactions with the important catalytic triad of dengue virus protease enzyme; Ser135, His51, and Asp75, which are mainly involved in antidengue activity. [171] Therefore, the compound can be regarded a viable candidate for a new agent to inhibit dengue virus type 2 and should be experimentally validated to confirm the predicted efficacy.…”
Section: In Silico Studymentioning
confidence: 99%
“…In search of potential drug candidates against dengue, Habibi et al developed a new series of diarylpentanoid derivatives and found in silico 1‐(3‐chloropropyl)−3,5‐bis[( E )−4‐methoxybenzylidene]piperidin‐4‐one (compound 53 ) with significant potential anti‐dengue activity as this compound has a higher binding energy (−6.40 kcal/mol) toward dengue type 2 NS2B/NS3 protease protein than the positive control panduratin A (−5.18 kcal/mol). [ 171 ] This diarylpentanoid derivative also forms hydrophobic and hydrophilic interactions with the important catalytic triad of dengue virus protease enzyme; Ser135, His51, and Asp75, which are mainly involved in anti‐dengue activity. [ 171 ] Therefore, the compound can be regarded a viable candidate for a new agent to inhibit dengue virus type 2 and should be experimentally validated to confirm the predicted efficacy.…”
Section: In Silico Studymentioning
confidence: 99%
“…To replicate, the DENV-2 virus requires a protein complex protease (NS3) and its cofactor (NS2B), namely the NS2B/NS3 serine protease. The NS3 protein (which is assisted by NS2B as a cofactor) is a protein that has a vital role in the process of proteolytic and viral replication (Habibi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%